Diversity and Growth Characteristics of Tree Species in the Botanical Gardens, University of Ibadan, Nigeria - A.F, Aderounmu; Onilude, Q.A; Oladele, A.T (Journal of Forests, 2017)
This study assessed the diversity and growth characteristics of tree species in University of Ibadan Botanical Gardens with a view to provide data for improved management of the garden. Ten plots (25m x 25m) were sampled randomly in the garden. Growth parameters evaluated included: total and merchantable height, diameter at breast height, diameters at middle, base and top. Descriptive statistics of the growth characteristics of the tree species revealed a mean volume of 20.03+ 2.91m3/ha and 0.45+0.79m2/ha for basal area. Afzelia africana had the highest tree volume (72.42m3) followed by Vitex doniana (50.10m3) while the least volume was observed in Terminalia cattapa (5.57m3). Cedrela odorata (15.3%) had highest frequency of individual trees followed by Delonix regia (4.2%) while 12 species had single tree each (1.4%). Low Slenderness coefficient (SLC) of < 70 showed that most tree species in the garden are not susceptible to wind induced damage. Only Enterolobium cyclocarpum possessed moderate SLC which could be vulnerable to wind velocity despite some form of resistance. Further research centered on tree form and growth parameters need be encouraged for improved management of the botanical garden.